Revealing a Life-World Perspective for Urban Planning: Conceptual Reflections and Empirical Evidence from Peri-Urban Maputo (Mozambique) - Axel Prestes Dürrnagel; Eberhard Rothfuß; Thomas Dörfler (Land)
Cities in sub-Saharan Africa are growing at an unprecedented rate, resulting in the significant expansion of peri-urban spaces. Postcolonial planning reflects the instrumental rationale continued by colonial legacies and largely fails to take the realities of the peri-urban population into account. As the example of Maputo, the Mozambican capital, demonstrates, the consequences are far-reaching. Implementing individual land titling programs promotes the commodification of space and the individualization of collective life, while the modernist vision of a homogeneous physical order leads to the socio-spatial alienation of existing residents and large-scale displacements. Employing a life-world approach in Alfred Schütz’s tradition, this paper brings the everyday reality of peri-urban dwellers into focus, offering a renewed planning agenda. Building on place-based research and life-world analytical ethnography, the reconstruction of practices and experiences illuminates the “paramount reality” of everyday life in Maputo as necessary entry points for an urban planning agenda that reconciles both the life-world of the people and the instrumental realities of state and planning actors. Applying a life-world perspective to urban planning reveals a realistic and inclusive approach grounded in the experience and social reality of the people living in the “ordinary city”.